PENINGKATAN KOMPETENSI MENULIS PUISI SISWA SMA DENGAN STRATEGI EKONEK - Teguh Pramono Pramono; Sumadi Sumadi; Ah Roifuddin (Fakultas Sastra Universitas Negeri Malang, 2013)
The students’ writing competence in State Senior High School Pagak I in composing poetry is still low as they have problems to brainstorm ideas and use poetic devices . Therefore, this classroom action research was proposed to develop students’ writing competence in composing poetry through the use of Ekonek strategy (exploration, construction, elaboration, and confirmation) on (1) idea extraction, (2) idea arrangement, and (3) imagery development, diction, theme and meaning, figure of speech, rhyme and rhythm, and typography. The subjects of this research are 20 students consisting of 3 boys and 17 girls. The result of this research shows an increase in students’ competence indicated by their gain 25,88 from the average of the first poetry test 56,14 becomes 82,02 in the last test. The development of this result has impacted on the increase of the students’ quantity who can reach the minimum completeness criteria (KKM), which is about10,53% in pre-cycle becomes 89,47 in post-cycle